(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
All human beings without exception, are in some way or the other, consumers of goods & services. Thus, a day in the life of a person is full of consumer decisions. Cognitive bias can have a significant impact on the decisions and judgments people make, often resulting in deviations from rational thinking and decision making. This applies to consumer decisions as well. Marketing literature mentions cognitive biases that influence consumer decision making. The present paper focuses on six cognitive biases that affect decision making of consumers & tries to study their influence on a consumersacross demographic factors. It also investigates which bias / biases exert the major influence on the buying process, how consumers view their own buying behaviour & how marketers use the cognitive biases for their advantage. The paper is based on empirical research.